MANAJEMEN PENDIDIKAN ADAB DI PESANTREN TQH AL-HASYIMI TENGGULUN SOLOKURO LAMONGAN - shafwan, Muhammad Hambal; Hasna, Hana Nadiatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to discuss how to manage adab education at the TQH al-Hasyimi Tenggulun Solokuro Lamongan Islamic Boarding School. This research is qualitative research with a case study approach, which means this research was conducted in a natural context to understand the phenomena that occur. The methods used include various techniques to carry out in-depth interpretation of the phenomenon. The results of this research explain that adab education at the TQH al-Hasyimi Islamic boarding school uses the book